2019
DOI: 10.1002/ijc.32104
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic factors and the risk of colorectal cancer by KRAS and BRAF mutation status

Abstract: Factors related to energy metabolism and the metabolic syndrome, such as higher body mass index (BMI), blood glucose, or blood lipids, and blood pressure, are associated with an increased risk of colorectal cancer (CRC). However, CRC is a heterogeneous disease, developing through distinct pathways with differences in molecular characteristics and prognosis, and possibly also in risk factors. For subtypes defined by KRAS and BRAF mutation status, BMI is the only metabolic factor previously studied, with inconsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
0
20
2
Order By: Relevance
“…Among the 1,003 CRC patients with BRAF test, 23 patients with a positive BRAF mutation was found with a mutation rate of 2.29% -much lower than that in the published data of 8-10% (Bahrami et al, 2018;Myte et al, 2019). This result indicated that BRAF mutation rate was specifically low in eastern China patients.…”
Section: Braf Mutation Was Specifically Low In Eastern China Crc Patimentioning
confidence: 62%
See 1 more Smart Citation
“…Among the 1,003 CRC patients with BRAF test, 23 patients with a positive BRAF mutation was found with a mutation rate of 2.29% -much lower than that in the published data of 8-10% (Bahrami et al, 2018;Myte et al, 2019). This result indicated that BRAF mutation rate was specifically low in eastern China patients.…”
Section: Braf Mutation Was Specifically Low In Eastern China Crc Patimentioning
confidence: 62%
“…The most frequent mutation point of BRAF is V600E. The incidence of the BRAF V600E mutation is estimated to be about 8-10% in CRC patients (Bahrami et al, 2018;Myte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Associations between environmental factors and KRAS status have not been extensively investigated. Only a few studies have reported inconsistent findings regarding associations between BMI/metabolic parameters and KRAS status [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…CRC is heterogeneous cancer that is caused by multiple risk factors (12,13). Tumor heterogeneity as the greatest challenges must be considerable (14).…”
Section: Introductionmentioning
confidence: 99%